Surface engineering of light alloys : aluminum, magnesium and titanium alloys - Dong, Hanshan (Woodhead Publishing in materials., 2010)
The growing use of light alloys in industries such as aerospace, sports equipment and biomedical devices is driving research into surface engineering technologies to enhance their properties for the desired end use. Surface engineering of light alloys: Aluminium, magnesium and titanium alloys provides a comprehensive review of the latest technologies for modifying the surfaces of light alloys to improve their corrosion, wear and tribological properties.Part one discusses surface degradation of light alloys with chapters on corrosion behaviour of magnesium alloys and protection techniqu.